Seção de Conservação e Manutenção - Pires, Jair Rogério; Corte, Norival; Souza, Wilson de; Ozelim, Luiz Carlos; Prestes, Carlos Alexandre; Corassi, Sidinei; Silva Junior, Osmar Castro; Costa Filho, Geraldo; Martines, William Rodrigues; Vitte, Marcos Antonio; et al. (ARCHIVES OF HEALTH INVESTIGATION, 2013)
Apresentação - Marcos Antonio Vitte